2016
DOI: 10.1007/s11250-016-1031-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of desho grass (Pennisetum pedicellatum) hay as a basal diet for growing local sheep in Ethiopia

Abstract: The study was conducted to determine feed intake, digestibility, and body weight (BW) change of Washera sheep fed on desho grass and natural pasture hay as a basal diet and supplemented with concentrate mixtures. Twenty-five intact male sheeps with body weight of 19.4 ± 1.89 kg (mean ± SD) were used in randomized complete block design. The dietary treatments were 100% natural pasture hay (NPH) (T1), 75% NPH + 25% desho grass hay (DGH) (T2), 50% NPH + 50% DGH (T3), 25% NPH + 75% DGH (T4), and 100% DGH (T5). Equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
2
2
6
Order By: Relevance
“…In the current study, the CP content of desho grass hay is relatively higher than the value of the previous result reported by Asmare et al. (2016) 8.6%, 7.5% planted in the mid and high altitude areas of Ethiopia respectively. The deviation of current result from previous reports might be due to drying process, storage, stage of maturity and differences in the growing environment (Biniyam et al., 2018).…”
Section: Discussioncontrasting
confidence: 85%
“…In the current study, the CP content of desho grass hay is relatively higher than the value of the previous result reported by Asmare et al. (2016) 8.6%, 7.5% planted in the mid and high altitude areas of Ethiopia respectively. The deviation of current result from previous reports might be due to drying process, storage, stage of maturity and differences in the growing environment (Biniyam et al., 2018).…”
Section: Discussioncontrasting
confidence: 85%
“…( 2019 ), respectively. Regarding findings in Ethiopia, the current CP value is higher than reported by Asmare et al (2016) and Gelgelo et al (2017) , 3.5 and 3.73%, but lower than the value 9.81% reported by Gebregiorgis et al. ( 2017 ), respectively.…”
Section: Discussioncontrasting
confidence: 76%
“…However, the current value is lower than the values 94.53 and 95.75% reported by Kibrom (2017) andGetent et al (2019), respectively. Regarding findings in Ethiopia, the current CP value is higher than reported by Asmare et al (2016) and Gelgelo et al (2017), 3.5 and 3.73%, but lower than the value 9.81% reported by Gebregiorgis et al (2017), respectively. The CP content of NPH used in the current study was below the minimum level (7%) required for maintenance in ruminant animals (Van Soest 1994).…”
Section: Chemical Composition Of the Experimental Feeds And Refusalscontrasting
confidence: 76%
See 1 more Smart Citation
“…Larger areas of farm land allocation for forage production by a majority of the farmers in project intervention areas may be related to better provision of seed/ planting material and better adoption of improved forages for their multiple roles including as a source of cash. is indicated that choice of niches in the study area depends on the availability of planting material and the level of production [32,33] rather than farm land size which was not consistent according to a report by Njarui et al [34]. Moreover, larger farm land allocations of a greater number of farmers in the project intervention area indicated a strong interest of farmers for improved forage production if they are provided planting material with necessary training on production and utilization systems.…”
Section: Niches Adopted and Land Allocation For Foragementioning
confidence: 83%